2019
DOI: 10.17478/jegys.570501
|View full text |Cite
|
Sign up to set email alerts
|

Reading, Mind Mapping, and Sharing(RMS): Innovation of New Learning Model on Science Lecture to Improve Understanding Concepts

Abstract: The course of science is considered to boring and difficult course to be understood by students of science education program. The aims of this research are examine the effect of RMS learning model in mastering the students concepts; 2) examine the effect of difference academic ability in mastering students concept; 3) examine the effect of interaction between RMS learning model and different academic abilities on mastering students concepts. The method of this research is using quasi experimental design method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 15 publications
(11 reference statements)
2
24
0
5
Order By: Relevance
“…ERP instructional model is developed by using a learning concept based research. Several reasons are used as the basic rationale in using learning-based research: (1) Research becomes one of important aspects in higher education [17] and the learning trend currently [18]; (2) It integrated learning-based research activities that can improve students' learning outcomes [19] and learning based contextual problems [20], [21] because it facilitates students to construct the knowledge independently so as students understand and evaluate the concepts that have been learned [17], [22]; (3) Learning outcomes that encompasses cognitive, affective, and psychomotor can be achieved by students by applying research activities integrated in teaching and learning process [23]. It is therefore hoped that by using ERP instructional model that comprises research activities provides the students to acquire HOTs in science and social science learning.…”
Section: Resultsmentioning
confidence: 99%
“…ERP instructional model is developed by using a learning concept based research. Several reasons are used as the basic rationale in using learning-based research: (1) Research becomes one of important aspects in higher education [17] and the learning trend currently [18]; (2) It integrated learning-based research activities that can improve students' learning outcomes [19] and learning based contextual problems [20], [21] because it facilitates students to construct the knowledge independently so as students understand and evaluate the concepts that have been learned [17], [22]; (3) Learning outcomes that encompasses cognitive, affective, and psychomotor can be achieved by students by applying research activities integrated in teaching and learning process [23]. It is therefore hoped that by using ERP instructional model that comprises research activities provides the students to acquire HOTs in science and social science learning.…”
Section: Resultsmentioning
confidence: 99%
“…Questioning and answering activity in the QASEE learning model are reported to be able to encourage the pre-service teachers to ask higher level questions better than just answering questions from the lecturers or even after the implementation of blended learning model (YeÅŸil & Korkmaz, 2010). Likewise in the sharing activity, it is mentioned that the dialogue within the group (sharing) could encourage pre-service teachers to produce better questions (Bielik & Yarden, 2016;Kaya & Temiz, 2018) and increase their comprehension (Kaya & Temiz, 2018;Muhlisin, 2019;Olde Bekkink et al 2015). This condition certainly has an effect on the class discussion activities later, where the pre-service teachers are welcome to ask questions verbally over the learning material presented by other groups.…”
Section: Question Types Based On Cognitive Process Dimensionmentioning
confidence: 99%
“…Unfortunately, the earlier researchers have found that the practical activities in the school are not achieving the required objectives due to insufficient learning strategies (Muhlisin, 2019). The results of Lin Zang's research showed that the instructional conditions affected students' learning of energy transfer in knowing and reasoning, but not in applying.…”
Section: Introductionmentioning
confidence: 99%